2017
DOI: 10.1002/anie.201704672
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Electrophilic Fluorination of Alkylcarbastannatrane Reagents

Abstract: We report the use of isolable primary and secondary alkylcarbastannatrane nucleophiles in site-specific fluorination reactions. These reactions occur without the need for transition metal catalysis or in situ activation of the nucleophile. In the absence of the carbastannatrane backbone, alkyltin nucleophiles exhibit no activity towards fluorination. When enantioenriched alkylcarbastannatranes are employed, fluorination occurs predominately via a stereoinvertive mechanism to generate highly enantioenriched alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 53 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…After Louis Pasteur discovered chirality by separating the enantiomers of (±)-ammonium-tartrate, it has become a very important topic in natural science. Nevertheless, even today, the fundamental question of chirality’s origin is not answered yet satisfactorily. Metallatranes also contain chiral information. They are propeller-type molecules, and the atrane cages can be Λ- or Δ-configured. A second characteristic feature of these compounds is the intramolecular N→M (M = metal, metalloid) coordination, the strength of which depends on the identity of the axial substituent.…”
Section: Introductionmentioning
confidence: 99%
“…After Louis Pasteur discovered chirality by separating the enantiomers of (±)-ammonium-tartrate, it has become a very important topic in natural science. Nevertheless, even today, the fundamental question of chirality’s origin is not answered yet satisfactorily. Metallatranes also contain chiral information. They are propeller-type molecules, and the atrane cages can be Λ- or Δ-configured. A second characteristic feature of these compounds is the intramolecular N→M (M = metal, metalloid) coordination, the strength of which depends on the identity of the axial substituent.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the fluoromethylated compounds have widespread applications in agrochemicals, pharmaceuticals, and materials . Conventionally, the fluoromethylated compounds are prepared via C–H fluorination of CH 3 -containing compounds or fluorination of functionalized substrates . However, these methods have some limitations, such as narrow substrate scope, low regioselectivity, or prior installation of a functional group.…”
mentioning
confidence: 99%
“…This approach enabled the first example of a stereospecific cross-coupling reaction using an unactivated secondary organotin species . Subsequently, we extended this chemistry to stereospecific acylation reactions, as well as stereospecific fluorination reactions. , …”
mentioning
confidence: 99%
“…For instance, desilylation of 12 was readily achieved by treatment with TBAF. Previously, we have demonstrated that diborylation of olefins and LiAlH 4 reduction of esters do not affect the integrity of the carbastannatrane unit. ,, The majority of the enantioenriched alkylcarbastannatranes prepared using this method contain a methyl group on the stereogenic carbon center. Unfortunately, analytical chiral HPLC conditions could not be found to separate enantiomers of carbastannatrane 13 , in which an ethyl group replaces the methyl group.…”
mentioning
confidence: 99%